Adiponectin and Its Role in Inflammatory Process of Obesity - Ami Febriza; Ridwan Ridwan; Suryani As'ad; Vivien Novarina Kasim; Hasta Handayani Idrus (Molecular and Cellular Biomedical Sciences, 2019)
Obesity is a chronic, low degree systemic inflammatory status. Microarray examination shows a disturbance in the expression of cytokine, chemokine, complementary protein and half of the other acute phase components in obese patients. Adiponectin is the hormone that increases insulin sensitivity, while its level decreases under condition of fatty tissue enlargement that occurs in obesity. Excessive weight causes the adipocyte cells and adipose tissues produce various types of mediators. The inflammatory process is the main cause of metabolic diseases, and the main role of adipose tissue in the inflammatory process is determined by the production of pro-inflammatory mediators and anti-inflammatory mediators. Adiponectin has an important anti-inflammatory effect on obesity. Adiponectin has an important anti-inflammatory effect on obesity. Adiponectin works on macrophage and monocyte to inhibit the production of pro-inflammatory cytokine and increase the expression of interleukin (IL)-10 and IL-1 receptor antagonists. Adiponectin reduces induction of intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 endothelial adhesion by TNF-α or resistin. In obese patients, it is characterized by resistance to adiponectin alongside a decrease and the possibility of adiponectin loss in the receptor population in liver and muscles, leading to low adiponectin level.Keywords: adiponectin, obesity, inflammation